2019
DOI: 10.29244/jfs.3.1.53-72
|View full text |Cite
|
Sign up to set email alerts
|

Gender Relations and Subjective Family Well-Being Among Farmer Families: A Comparative Study Between Uplands and Lowlands Areas in West Java Province, Indonesia

Abstract: <p>The objectives of this study are described as follows: (1) To examine the conditions of<br />social, economic and demographic characteristics of poor farmer families who live at<br />uplands and lowlands areas, (2) to describe the social-cultural and agroecosystem<br />conditions of poor farmer families who live at uplands and lowlands areas, (3) To<br />explain type of gender relations of poor farmer families who live at uplands and<br />lowlands areas, and (4) to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…The same thing was found by Hapsari et al (2017) in six districts in East Java the majority of men were found working in agriculture during the day, while women were at home. Puspitawati et al (2018) state that in general, gender roles in agricultural activities, in terms of access and control of agricultural resources, are dominated by men. Role differentiation is a structural prerequisite for family survival.…”
Section: Farmers Characteristics Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…The same thing was found by Hapsari et al (2017) in six districts in East Java the majority of men were found working in agriculture during the day, while women were at home. Puspitawati et al (2018) state that in general, gender roles in agricultural activities, in terms of access and control of agricultural resources, are dominated by men. Role differentiation is a structural prerequisite for family survival.…”
Section: Farmers Characteristics Gendermentioning
confidence: 99%
“…Role differentiation is a structural prerequisite for family survival. If women must continue to be involved in aren farming (yield utilization) which requires continued presence and time, it will create a family imbalance that can lead to the achievement of wrong family goals (Puspitawati et al 2018).…”
Section: Farmers Characteristics Gendermentioning
confidence: 99%
“…According to Agarwal (1994), social norms about the role of women, as justified by tradition and religion, can prevent women from being involved in agriculture. In Indonesia, women are perceived as mostly occupied with child-rearing and domestic activities, women allocate labour to agriculture, but agricultural activities and decisions are considered men's domain (Herartri 2005;Puspitawati et al 2018). This further leads to women's lower participation in extension programs and limited access to land and agricultural inputs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In general, women's roles in Indonesia are likely influenced by tradition, religious beliefs, plantation politics during Dutch colonialism, and dogmatic government during the New Order era from 1966 to 1998 (Backues 1992;Koning et al 2000). In rural Indonesia, men are regarded as the head of the family and the primary decision-maker (Herartri 2005;Puspitawati et al 2018). The traditional roles for wives and husbands emphasise that a woman's place is in the domestic sphere; where men are responsible for family income while women run the household and take care of the children (Herartri 2005;Puspitawati et al 2018).…”
Section: Women In Agriculture In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation